The educational construction of human beings in the Quran is an analytical study - Al-Baghdadi, Prof Dr. Ameed Abdullah; Hanna, Ass.Prof Dr. Ali Shmaoon; Alwan, Rana Amer (Thi Qar Arts Journal, 2023)
1